2018
DOI: 10.1038/s41467-018-05626-2
|View full text |Cite
|
Sign up to set email alerts
|

Notch3-dependent β-catenin signaling mediates EGFR TKI drug persistence in EGFR mutant NSCLC

Abstract: EGFR tyrosine kinase inhibitors cause dramatic responses in EGFR-mutant lung cancer, but resistance universally develops. The involvement of β-catenin in EGFR TKI resistance has been previously reported, however, the precise mechanism by which β-catenin activation contributes to EGFR TKI resistance is not clear. Here, we show that EGFR inhibition results in the activation of β-catenin signaling in a Notch3-dependent manner, which facilitates the survival of a subset of cells that we call “adaptive persisters”.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 63 publications
3
50
0
Order By: Relevance
“…Activation of several signaling transducers were associated with persistent drug tolerance to EGFR TKI treatments, including Akt, Notch, and Casein Kinase 1. 49 , 50 , 51 These transducers are not miR-146b-5p targets and may contribute to the survival of PC9/ge-miR-146b-5p cells in high concentration of gefitinib. The phenomenon was reported in previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of several signaling transducers were associated with persistent drug tolerance to EGFR TKI treatments, including Akt, Notch, and Casein Kinase 1. 49 , 50 , 51 These transducers are not miR-146b-5p targets and may contribute to the survival of PC9/ge-miR-146b-5p cells in high concentration of gefitinib. The phenomenon was reported in previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Combined inhibition of EGFR and Notch 3 using pan-Notch GSIs was able to reverse the stem-like phenotype [ 158 ]. Subsequent work showed that EGFR TKI activation of Notch 3 in EGFR-mutant lung cancer cells is accompanied by stabilisation and activation of β-catenin [ 159 ].…”
Section: Notch Crosstalk With Other Signalling Pathways and Therapmentioning
confidence: 99%
“…Interestingly, in this latter phenomenon, the observed tumor driving induction effect of Notch3 seems to be dependent on direct physical (biochemical) interaction with EGFR and Notch3 tyrosine phosphorylation modification, although the exact residue(s) undergoing this posttranslational regulation has not yet been identified [101]. Remarkably, it should be noted that while Notch3 mediates EGFR regulation of the Wnt/β-catenin pathway in EGFR mutant NSCLC, a dominant negative form of Mastermind-like (dn-MAML) is ineffective in preventing the expansion of ALDH + CSCs in these tumors, indicating that Notch3 action is likely due to non-canonical activity [102]. Notably, in Kras-mutant ACL tumor cells upregulation of Notch3 expression has also been observed in a signaling pathways' interplay requiring PKCι-mediated ELF3 phosphorylation and the subsequent Notch3 promoter occupancy and transcriptional activation that, furthermore, leads to enhanced CSC phenotype [103].…”
Section: Notch and Nsclcmentioning
confidence: 99%